Analisis Perbandingan BPJS Kesehatan dan Asuransi Swasta dalam Efisiensi Layanan dan Persaingan Bisnis - Ane Aryanti; Khairunnisa; Nessa A’syifa Putri Andrika (Program Studi Ilmu Hukum, Universitas Kuningan, 2025)
This study aims to analyze the comparison between BPJS Kesehatan (Indonesia’s national health insurance) and private health insurance in terms of service efficiency and business competition strategies. Using a literature review method, the research examines various aspects such as cost and premiums, service access, facilities, claims procedures, and patient satisfaction. The findings reveal that BPJS Kesehatan excels in providing broad coverage at affordable premiums, though it still faces challenges in service speed and referral systems. On the other hand, private health insurance offers faster, more flexible, and premium-level services, albeit at higher costs. Additionally, both systems have begun collaborating through the Coordination of Benefit (CoB) scheme to provide dual advantages for participants. This study offers important insights for the development of a more efficient and competitive health insurance system in Indonesia.